2016
DOI: 10.1007/s11325-016-1411-3
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea (OSA) and clinical depression—prevalence in a sleep center

Abstract: The prevalence of clinical depression according to ICD-10 criteria in a selected clinical sample (referred to the sleep center) was 21.5 %. Mood scales tend to overestimate complaints as compared to psychiatric consultation. Interdisciplinary cooperation is recommended for both OSA patients with symptoms of depression and depressed patients with treatment resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 62 publications
1
18
0
2
Order By: Relevance
“…We found that 3 months of CPAP treatment of patients with OSA had a beneficial effect on the level of depressive and trait anxiety symptoms (Acker et al, 2017;BaHammam et al, 2016;Ejaz et al, 2011;Fidan et al, 2007;Naqvi et al, 2014;Ryan, Bayley, Green, Murray, & Bradley, 2011;Sanchez, Buela-Casal, Bermudez, & Casas-Maldonado, 2001). These effects were highly significant, because they survived Bonferroni correction.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…We found that 3 months of CPAP treatment of patients with OSA had a beneficial effect on the level of depressive and trait anxiety symptoms (Acker et al, 2017;BaHammam et al, 2016;Ejaz et al, 2011;Fidan et al, 2007;Naqvi et al, 2014;Ryan, Bayley, Green, Murray, & Bradley, 2011;Sanchez, Buela-Casal, Bermudez, & Casas-Maldonado, 2001). These effects were highly significant, because they survived Bonferroni correction.…”
Section: Discussionmentioning
confidence: 73%
“…Higher depression is caused by daytime sleepiness, and the resulting fatigue and, vice‐versa, higher level of depressive symptoms can be understood as a risk factor in the development of EDS (Aloia et al, ; Antic et al, ). We found that 3 months of CPAP treatment of patients with OSA had a beneficial effect on the level of depressive and trait anxiety symptoms (Acker et al, ; BaHammam et al, ; Ejaz et al, ; Fidan et al, ; Naqvi et al, ; Ryan, Bayley, Green, Murray, & Bradley, ; Sanchez, Buela‐Casal, Bermudez, & Casas‐Maldonado, ). These effects were highly significant, because they survived Bonferroni correction.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Research has shown an association between depressive symptoms and OSA 10. Depressive symptomatology has been documented in 21.5% of patients surveyed for sleep apnea 11. Additionally, a high prevalence of depressive symptoms was detected among individuals with a high likelihood of OSA 12,13.…”
Section: Introductionmentioning
confidence: 99%